Challenges of Internal Auditing in the Indonesian Government - Mirna Amirya (Jurnal Ilmiah Akuntansi, 2024)
There is an essential need for comprehensive research into innovative audit strategies specifically designed to address the persistent challenges faced by internal auditing within Indonesia's government sector. This study delves deeply into these challenges, highlighting the critical role of internal auditing in fostering transparent and accountable financial management across government agencies. By adopting a qualitative research methodology, the study employs a literature review combined with thematic descriptive analysis. The findings from the literature review underscore the indispensable role of internal auditing in improving accountability, transparency, and overall performance of government entities. However, several significant obstacles hinder these benefits. The challenges identified include difficulties in adopting and implementing advanced technology within the audit process, ensuring the independence of internal auditors from the entities they audit, the effectiveness of audits in detecting and preventing corruption, and the ongoing need to enhance the qualifications and training of internal auditors. These challenges are critical as they impact the efficacy of internal audits in fulfilling their role as watchdogs of public funds and as enhancers of public trust. Addressing these issues through targeted research and policy intervention is crucial for advancing the capabilities and impact of internal auditing within the Indonesian government. The study advocates for a strategic focus on developing adaptive audit techniques and training programs that align with the evolving demands of the governmental audit environment.